Distinctive genotypes in infants with T‐cell acute lymphoblastic leukaemia. (24th July 2015) - Mansur, Marcela B.; van Delft, Frederik W.; Colman, Susan M.; Furness, Caroline L.; Gibson, Jane; Emerenciano, Mariana; Kempski, Helena; Clappier, Emmanuelle; Cave, Hélène; Soulier, Jean; Pombo‐de‐Oliveira, Maria S.; Greaves, Mel; et al.
Summary: Infant T‐cell acute lymphoblastic leukaemia (iT‐ALL) is a very rare and poorly defined entity with a poor prognosis. We assembled a unique series of 13 infants with T‐ALL, which allowed us to identify genotypic abnormalities and to investigate prenatal origins. Matched samples (diagnosis/remission) were analysed by single nucleotide polymorphism‐array to identify genomic losses and gains. In three cases, we identified a recurrent somatic deletion on chromosome 3. These losses result in the complete deletion of MLF1 and have not previously been described in T‐ALL. We observed two cases with an 11p13 deletion ( LMO2 ‐related), one of which also harboured a deletion of RB1 . Another case presented a large 11q14·1‐11q23·2 deletion that included ATM and only five patients (38%) showed deletions of CDKN2A/B . Four cases showed NOTCH1 mutations; in one case FBXW7 was the sole mutation and three cases showed alterations in PTEN . KMT2A rearrangements ( KMT2A‐r ) were detected in three out of 13 cases. For three patients, mutations and copy number alterations (including deletion of PTEN ) could be backtracked to birth using neonatal blood spot DNA, demonstrating an in utero origin. Overall, our data indicates that iT‐ALL has a diverse but distinctive profile of genotypic abnormalities when compared to T‐ALL in older children and adults.